2023
DOI: 10.1039/d3sm00017f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-level insights into a tripolyphosphate and pyrophosphate templated membrane assembly

Abstract: Templated assembly of small molecules into nano-structural architectures has been used extensively by nature throughout its evolution. These systems were also studied in artificial systems to design phosphate templated assembly....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
(117 reference statements)
1
4
0
Order By: Relevance
“…Similar experiments with OLEA-ADP suggest that it was less tolerable in the presence of Mg 2+ , and we found a clear solution at 4.0 mM Mg 2+ (Figure S16A). These experiments support the role of electrostatic and ionpair interactions 16,45 in forming vesicular assemblies. Thus, the number of phosphate units, the electrostatic and ion-pair interactions control the templated assembly of the protocellular membrane.…”
Section: Prebiotic Synthesis Of Ethanolamine-based Lipidssupporting
confidence: 69%
See 3 more Smart Citations
“…Similar experiments with OLEA-ADP suggest that it was less tolerable in the presence of Mg 2+ , and we found a clear solution at 4.0 mM Mg 2+ (Figure S16A). These experiments support the role of electrostatic and ionpair interactions 16,45 in forming vesicular assemblies. Thus, the number of phosphate units, the electrostatic and ion-pair interactions control the templated assembly of the protocellular membrane.…”
Section: Prebiotic Synthesis Of Ethanolamine-based Lipidssupporting
confidence: 69%
“…Similar to this, it may be possible that OLEA with a terminal positive charge (ammonium headgroup) and a shorter dodecyl chain might be assembled with ATP. Recently, we have shown the templated assembly of choline-based amphiphiles in the presence of tripolyphosphate . To investigate the ATP-templated assembly of ethanolamine-based lipids (OLEA), we mixed OLEA and ATP at various ratios in water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group proposed that apart from the anionic amphiphiles, cationic amphiphiles were also important in protocell formation and catalysis. Particularly, we have shown that a lysine-based prebiotic cationic amphiphile and anionic fatty acids may work in tandem (catanionic complex formation) to form a prebiotic membrane at low CVC and assisted in regioselective peptide bond formation . The protocell forming ability of the mixture of cationic amino acid-based amphiphiles (lysine octyl ester, LysOct) and anionic fatty acid amphiphiles (decanoic acid) led to a window of opportunities to explore the capabilities of phosphate- and sulfate-based anionic amphiphiles.…”
Section: Introductionmentioning
confidence: 99%